2021
DOI: 10.1016/j.indcrop.2021.113495
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in mechanical, physical and biological properties of eucalyptus and pine woods by raw pine resin in situ polymerization

Abstract: A raw pine resin, which is a cheap, renewable and easily obtainable forest resource, was used to impregnate two different fast-growing solid woods (Eucalyptus grandis Hill Maiden and Pinus elliottii Engelm) and in situ polymerized to improve their hygroscopic, chemical, morphological, mechanical, and thermogravimetric properties. Biodegradation resistance against subterranean termites and white-rot fungus was also addressed. The treatment yielded changes in colorimetric properties, dimensional stability and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 56 publications
0
7
0
4
Order By: Relevance
“…Because of this, microorganisms have difficulty degrading these rice straws compared to the degradation of human fecal matter. Biochemical degradation of lignin explains the general limitation role of bacteria in the degradation of lignin macromolecules since bacteria are only responsible for the decomposition of side chains and monomers [32]. Likewise, the results presented by [18,33] both worked on lignin degradation and shown that bacteria can detach the aliphatic side chains from the molecule but that the phenol-ether bonds remained non-localized by the bacteria.…”
Section: Presentation and Discussion Of The Trend Of The Biogasmentioning
confidence: 93%
“…Because of this, microorganisms have difficulty degrading these rice straws compared to the degradation of human fecal matter. Biochemical degradation of lignin explains the general limitation role of bacteria in the degradation of lignin macromolecules since bacteria are only responsible for the decomposition of side chains and monomers [32]. Likewise, the results presented by [18,33] both worked on lignin degradation and shown that bacteria can detach the aliphatic side chains from the molecule but that the phenol-ether bonds remained non-localized by the bacteria.…”
Section: Presentation and Discussion Of The Trend Of The Biogasmentioning
confidence: 93%
“…This forest-based resource was oven dried at 50 • C until reaching a constant weight, milled using a Wiley mill, and then sieved using a 100-mesh screen. The resulting wood flour was characterized via wet-chemical analysis to obtain ethanol-toluene extractives [23], acid-insoluble lignin [24], ashes [25], and holocellulose (remaining mass percentage) contents.…”
Section: Fillers Preparation and Furfurylationmentioning
confidence: 99%
“…Nesse sentido, o desenvolvimento de novos tipos de tratamentos alternativos aos mais tradicionais, têm sido investigados, com o intuito de proporcionar variações positivas nas propriedades da madeira, que vão desde o aumento da resistência biológica até o incremento da estabilidade dimensional. Entre os estudos, destaca-se a polimerização in situ com monômeros [11,12], termorretificação [13,14] e impregnação com produtos naturais [15,16]. Assim, a busca por novas soluções, como os tratamentos superficiais, faz-se necessário para garantir a melhoria das propriedades deste tipo de madeira, com intuito de inibir a ação de agentes externos de degradação, a fim de proporcionar um desempenho e durabilidade satisfatórios.…”
Section: Introductionunclassified